ANALISIS TINGKAT KEBERHASILAN SISTEM PELANGGARAN SISWA MENGGUNAKAN MODEL DELONE & MCLEAN: (Studi Kasus Pada SMK Negeri 6 Kupang) - Domaking, Adriana; Enstein, Jhon; Benunifit, Yonly Adrianus (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2024)
This research aims to analyze the level of success of the student violation system at SMK Negeri 6 Kupang using the theoretical model developed by Delone & Mclean. The variables used in this research are system quality, information quality, service quality, user satisfaction, usage and net benefits. The object of this research is the student violation system owned by SMK Negeri 6 Kupang and the subjects of this research are 5 teachers who have qualifications as users of the student violation system. Based on the results of data analysis and hypothesis testing on the research questionnaire, conclusions can be drawn from calculating the perceptions of 5 respondents out of 93 teachers regarding items whose statements stated they were very good and good. This is proven by testing respondents' perceptions of the 6 variables contained in the Delone & Mclean (2003) model, namely system quality 90%, information quality 87%, service quality 89%, user satisfaction 92%, usage 80% and net benefits 94%. Testing of the hypotheses proposed in this research shows that all hypotheses are accepted. Next, the hypothesis test was carried out using the Pearson product moment correlation test. The test results proved that each variable in the Delone & Mclean model had an influence on the success of the student violation system at SMK Negeri 6 Kupang.